Near-fault seismic risk assessment of simply supported bridges. Issue 4 (November 2020) - Zhong, Jian; Jiang, Linwei; Pang, Yutao; Yuan, Wancheng
Bridges tend to sustain excessive seismic demand (e.g. displacement) under pulse-like ground motions attributing to the effect of forward directivity, which is of high likely to occur at locations near the fault rupture. This study tries to incorporate the pulse effect into the probabilistic seismic hazard analysis (PSHA) and probabilistic seismic demand analysis (PSDA) framework, which are combined to quantify the risk of earthquake-induced damage in the near-fault location. The near-fault PSDA and PSHA are established and connected conditioned on peak ground velocity (PGV). Four sets of typical simply supported bridge types with the varying heights, representing the range of the period, are simulated by taking account the strength and stiffness degradation associated with material and geometry nonlinearity. The detailed investigation of the near-fault seismic risk is performed for these bridge models located at representative near-fault sites namely 5, 10, 15, and 20 km, respectively. The results reveal that near-field directivity effect strongly impacts the bridge damage risk with the observation of higher risk at the closer site; the bridges with the period of approximately Tp /2(pulse period) tend to experience the highest seismic risk, and the relative vulnerability of four bridge types is also compared.